Approach for Optimal Selection of Innovative Actions for Residential Heating Systems - Andrii Polyvianchuk; Vasyl Petruk; Natalia Polyvianchuk; Kovalenko Yurii; Roman Semenenko; Olga Arsenyeva (Chemical Engineering Transactions)
Urban housing is the largest consumer of energy in European countries, representing approximately 43 % of total energy consumption. The objective of a sustainable society is to enhance the energy efficiency of buildings and domestic heating systems, with the goal of achieving zero-energy buildings that rely on renewable energy sources for their energy supply. To accomplish this, the current buildings must be effectively renovated. This study presents a method for upgrading household heating systems when there are limited finances available for investment. The proposed mathematical model is derived from the analysis of the building's energy system and combines the thermal energy producer and consumer into a unified system. It allows for the analysis of the building's condition using energy, environmental, and economic key indicators while also suggesting appropriate innovative measures. A proposed approach is to pick effective creative measures for the analysed building and optimise investment in time. The case study for the education building in Ukraine showed that the implementation of such an approach enables significant savings of up to 60-85 % of energy and fuel resources spent on building heat supply with a simultaneous reduction of environmental emissions by 39 % from the initial state.